Advanced Engineering Dynamics - Harrison, H R (John Wiley & Sons, 2012)
This book bridges the gap between elementary dynamics and advanced specialist applications in engineering. An approach has been adopted using standard terminology and notation in several subject areas, including road vehicle stability, aircraft stability, and robotics.